PEMBELAJARAN BIOLOGI BERBASIS INKUIRI UNTUK MENINGKATKAN KETERAMPILAN METAKOGNITIF, PEMAHAMAN KONSEP, DAN SIKAP ILMIAH SISWA KELAS X SMA - Rustininingsih, Anilia; Saptasari, Murni; Dahlia, Dahlia (Universitas Negeri Malang, 2017)
Biology learning is directed through scientific work processes to find out and prove something that can help students to gain a deeper understanding. This type of research is quasi experimental research. Research instruments used test sheets and a scientific attitude questionnaire. Data collection methods used are the test methods and dissemination of student's scientific attitude questionnaire. The data obtained were analyzed descriptively quantitative. The result showed that the difference of metacognitive skill of the experimental class students was 10.82, while the control class was 4.35. Understanding the concept of experimental class students gain the difference of 10.24, while the control class is 4.06. The experimental attitude of the experimental class students is 3.82 and the control class is 3.19. The results showed that metacognitive skills, conceptual understanding, and scientific attitudes of students using inquiry learning scored higher than those who did not use inquiry learning.